The Development of Blended Learning in Learning Evaluation Subject in Universities in Makassar City - Arnidah Arnidah; Syamsiah D; Andromeda Valentino Sinaga; Dedy Aswan (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this research is to develop a blended learning-based learning model in the Learning Evaluation Course. The research study implemented Research and Development approach. In this case, the researcher developed a product in universities using the Ken Peffers model. This model consists of five stages, namely identifying problems, determining goals and solutions, designing and developing products, demonstrating products, evaluating products, and communicating products. In this development procedure, the researcher demonstrated the product through some steps, including production, validation, and trial. The product was trialed through individual tests performed by exerts of media and learning material and course lecturers. Individual and small group trials were conducted to identify products and to improve the suitability of the learning objectives, materials, and media. The findings obtained from validation performed by experts of material and media indicate that the product developed is valid and practical to be tested.